An Exploratory Study on the Constraints for Entrepreneurial Activity: A Case of Micro and Small Enterprises in Kano, Nigeria - Abubakar, S. Garba; Shazali, Abu Mansor; Fariastuti, Djafar (The Journal of Applied Management and Entrepreneurship, 2013)
This paper explores the challenges confronting Nigerians, particularly women in entrepreneurial activity. The paper uses a qualitative approach to obtain the necessary information from micro and small entrepreneurs. In-depth interviews were conducted to collect data from 25 key informants who own micro and small enterprises that have been in operation for at least five years. The ualitative data was transcribed and presented in a narrative manner. The paper found liquidity constraints to be the most serious problem as most of the entrepreneurs cannot access microfinance from government agencies or microfinance institutions. It is also discovered that the participation of women in entrepreneurship is lower in comparison to their male counterparts. The existing microfinance policy should be revisited to ascertain loopholes that render the policy less effective. Close supervision of the microfinance institutions is needed to ensure compliance to ethical standards and practices in the issuance of credit and loans. To make more generalizable conclusions, similar studies are needed in Nigerian states where the participation of women is low.